Correlation between meat color and some indicators of carcass and meat quality of pigs - Kralik, Gordana; Kušec, Goran; Gutzmirtl, Hrvoje; Petričević, Antun; Grgurić, Dražen (Acta Agraria Kaposváriensis, 2002)
In this study, carcasses of 68 pigs from one test station in eastern Croatia were used. At the weight of approximately 100 kg pigs were slaughtered and measurements on the hot carcass were collected: hot carcass weight, carcass length (a and b), meat percentage (TP), and pH45. After 24 hours of cooling other quality indicators were measured: pH24, w.h.c., backfat and loin muscle areas. Pig carcasses weighted 78.79 kg (hot) and after 24 hours of cooling 77.32 kg. Mean values of the carcass length were 89.43 and 104.41 cm („a” and „b ”, respectively). The estimated mean leanness of pig carcasses was 54.28%, with backfat thickness of 17.25 mm and loin muscle depth 67.28. Areas of fat and loin muscle were 17.39 and 40.25 mm2, resp., while fat/meat ratio 0.44. Meat quality indicators showed good quality of the meat in average (pH45 was 6.19, pH24 5.71, w.h.c. 9.97, Minolta L* 53.04, a* 6.89 and b* 6.24. Medium strong, negative correlation was found between Minolta L* values and carcass length (-0.41 and -0.45, „a " and „b ", resp.), and backfat thickness TP (-0.34). Fat/meat surface ratio was negatively weak correlated with L* value (-0.29), while weak positive but significant r value was calculated between L* and MLD surface (0.28). The significant, weak and negative correlation was found between a* value and length „b” (-0.27). Correlations between Minolta values (L* and b*) and meat quality traits were also calculated. Strong, negative correlation was found between L* and pH24 values (-0.54). Between Minolta L* and pH45 values, the correlation was significant, medium strong and negative (-0.34). Medium strong and positive correlation was found for w.h.c. (0.44). Minolta a* value was negatively correlated with pH24 (-0.46) and pH45 (-0.33).